1999
DOI: 10.1046/j.1365-2842.1999.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of colour and hardness changes of soft lining materials in food colorant solutions

Abstract: The aim of this study was to measure the colour stability and viscoelastic properties of three commercially available soft lining materials in vitro, by exposing them to 3% erythrosine, tartrazine and sunset yellow solutions. The colour changes were determined using a computer controlled spectrophotometer. The colour change of three soft lining materials--Molloplast B, Flexor and Coe Super Soft--were determined after 1, 3 and 6 months storage in three different food colorant solutions. The colour changes of Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
1
15

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 23 publications
6
56
1
15
Order By: Relevance
“…However, according to manufacturers, the concentration of a colorant in some food products may reach 3%. These colorants are soluble in water and as they have electrostatic charges on their molecules, they may stain surfaces 50) . Interestingly, there was no significant difference between the effects of distilled water and food colorant solution.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to manufacturers, the concentration of a colorant in some food products may reach 3%. These colorants are soluble in water and as they have electrostatic charges on their molecules, they may stain surfaces 50) . Interestingly, there was no significant difference between the effects of distilled water and food colorant solution.…”
Section: Discussionmentioning
confidence: 99%
“…The application of soft lining materials with viscoelastic behavior close to that of mucosa has been reported to be preferable, compared to elastic materials such as silicone rubber-based soft lining materials in the clinical situation 1) . A hardness test, such as the Shore A hardness test has been employed by many researchers [14][15][16]24,25) . There was no significant difference between Shore A hardness of SR12F and MB.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the silicone rubber-based soft lining materials enhance the growth of fungi such as Candida albicans on the presence of saliva 13) . The materials are required to be minimally contaminated from the viewpoint of oral hygiene [14][15][16][17][18][19] . Fluorocarbon polymers have been applied to the dental field because of their excellent characteristics including chemical stability, water and oil repellency, and contamination resistance [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Although the experimental silicone elastomers with filler loadings of 6, 8 and 10 phr were found to have greater damping behavior and mechanical properties when compared with the commercial silicone soft lining materials, the SEM images in the previous study showed that the experimental silicone elastomers with filler loadings of 8 and 10 phr had high magnitude of silica agglomerates 11) . From this study, it was found that the experimental silicone elastomer with 6 phr silica loading had an acceptable viscosity to manipulate and had a comparable Shore A hardness to Molloplast-B 11,23) . In addition, lesser amounts of reinforcing fillers can reduce the cost of material production.…”
Section: Discussionmentioning
confidence: 83%
“…It was proposed that Shore A hardness of soft lining materials should be approximately 40 so that it does not injure the soft tissues and offers comfort to denture wearers. The most widely used heat-polymerized silicone soft lining material (Molloplast-B) was reported to have Shore A hardness 44 23) . In this study, the commercial soft lining materials (ST and RS) have higher Shore A hardness than the proposed value, therefore the experimental silicone elastomer with 6 phr silica loading (Shore A hardness 41.3) showed good potential for use as a soft lining material.…”
Section: Discussionmentioning
confidence: 99%